2017
DOI: 10.18203/2320-1770.ijrcog20175010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and symptomatology of polycystic ovarian syndrome in Indian women: is there a rising incidence?

Abstract: Background: Polycystic ovarian syndrome [PCOS] is a complex ill understood hormonal disorder resulting in myriads of symptoms like irregular menses, hyperandrogenism, metabolic disturbances and infertility. It occurs in about 8-11% of reproductive age group women. Recently changing lifestyles and rising obesity worldwide have contributed to rise in the incidence of PCOS. Objective of the present is to study the prevalence and symptomatology of PCOS in Indian women.Methods: 170 women in reproductive age group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 9 publications
3
37
2
Order By: Relevance
“…In the past 10 years, an increasing number of studies have assessed the prevalence of PCOS across the world. To date, seven nationally representative surveys have been conducted in India from 2010 to 2014, reporting a variation in prevalence from 6% to 46.8% . The lower prevalence of 4.21% observed in the present study might be due to the fact that Haryana is an agricultural state, with a relatively rural population with comparatively healthy lifestyles.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In the past 10 years, an increasing number of studies have assessed the prevalence of PCOS across the world. To date, seven nationally representative surveys have been conducted in India from 2010 to 2014, reporting a variation in prevalence from 6% to 46.8% . The lower prevalence of 4.21% observed in the present study might be due to the fact that Haryana is an agricultural state, with a relatively rural population with comparatively healthy lifestyles.…”
Section: Discussioncontrasting
confidence: 45%
“…In India, epidemiologic data regarding its prevalence and its complications are limited . Furthermore, most reports are region‐specific (mainly urban areas) and ignore urban/rural comparisons in terms of prevalence . It is likely that the prevalence of PCOS varies significantly between urban and rural regions owing to different environments, lifestyles, incidence of obesity, and dietary practices.…”
Section: Introductionmentioning
confidence: 99%
“…In present study we found the prevalence of PCOS to be 16.4 % in married women and 24 % in unmarried women. 19…”
Section: Discussionmentioning
confidence: 99%
“…It is a product of the complex interaction between genetic factors including prenatal exposure to high androgen levels, epigenetic factors, and environmental factors such as diet, physical activity, smoking and stress (Tsikouras et al 2015). Women with PCOS are susceptible to male type fat distribution due to 258 the effect of HA (Choudhary et al, 2017). In 2012, about 116 million women were affected by PCOS according to the WHO (Bharathi et al, 2017).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…In 2012, about 116 million women were affected by PCOS according to the WHO (Bharathi et al, 2017). PCOS occurs at a frequency of 11.2% of women of reproductive age and in 50% of teenage girls (Choudhary et al, 2017). Up to 70% of the women remain undiagnosed with PCOS.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%